Rancang Bangun Aplikasi Geofence Marketing Cafe Berbasis Android Studi Kasus: Ice Ah! - Afrizal Fath Rahman; Agi Putra Kharisma; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Ice Ah is a small business established since 11 April 2016 in Malang City. As a small business it is a very logic thinking that a business want to immediately attract people attention as a customer, because a business is vulnerable in their first year with a limited resource and competition with another business. For that reason the marketing ability become a necessary factor in a business growth, especially with a small business that make use of small scale customer. To improve the marketing ability in a business, a system that can do marketing functionality and targeting an area with a vary scale and also adjusting to customer location is needed. In this research the marketing system made there on application using geofence methodology with the information delivered as notification. Based on the test which have been done, all of the geofence marketing system functionality can work well with corresponding requirement which have been made, and having user experience value based on 6 scale with the value of Attractiveness 1.45, Perspicuity 1.725, Efficiency 1.4, Dependability 1.275, Stimulation 1.4375 and Novelty 1.0125. based on the benchmarking test with 246 other product generated a 6 scale comparison result with value of Attractiveness is above average, Perspicuity is good, Efficiency is above average, Dependability is above average, Stimulation is good and Novelty is above average.